Juridical Analysis of Consumer Protection in Electronic Transactions - Chairus Suriyat; Muhammad Salim Fauzi; Junaidi Lubis; Bambang Sutejo; Irma Herliza Rizki (Outline Publisher, 2025)
The increasing use of electronic transactions in the digital age has raised significant concerns regarding consumer protection. Consumers face various risks, such as fraud, product mismatch, delivery delays, and misuse of personal data. This research aims to analyze the juridical framework governing consumer protection in electronic transactions, particularly in Indonesia, where digital commerce is rapidly expanding. By applying a normative juridical method and qualitative analysis, the study reviews existing legislation, including Law No. 8 of 1999 on Consumer Protection, and evaluates its effectiveness in addressing current digital challenges. Findings show that despite having a legal framework, the enforcement and application of consumer protection laws in digital transactions remain limited and inconsistent. Many platforms do not fully comply with legal requirements related to transparency, dispute resolution, and data protection. The study includes statistical data and visual aids such as charts and tables to illustrate the scale of consumer issues in the digital environment. It concludes that there is a need for legal reform, stronger regulatory oversight, and greater platform accountability. Additionally, increasing public awareness and utilizing Alternative Dispute Resolution (ADR) mechanisms can enhance consumer protection in the growing e-commerce ecosystem.